The Phenomenology of the Body After 85 Years. (October 2021) - van Rhyn, Brianne; Barwick, Alex; Donelly, Michelle
The aim of this study was to describe the phenomenology of the body after 85 years, addressing the following question: What is the experience of the body at this age? Within the paradigm of existential phenomenology, this study was philosophically and methodologically underpinned by embodiment theory, positioning the body as the starting point for the exploration of lived experience. In-depth interviews with 20 purposively selected individuals were analyzed using van Manen's context-sensitive phenomenological orientation. Findings indicated that the body was experienced primarily in negative terms, as compromising engagement in meaningful activity, independence, safety, vitality, dignity, and identity. Participants coped with bodily changes through adaptation, humor, and acceptance. In addition, participants viewed their unreliable and at times unfamiliar body, as distinct from their sense of self. This research addresses the current lack of subjective accounts of bodily and embodied experiences in this group, combating assumptive views and contributing insightful understanding.